Is the Gut Microbiota a New Factor Contributing to Obesity and Its Metabolic Disorders? - Kristina Harris; Amira Kassis; Geneviève Major; Chieh J. Chou (Hindawi Limited, 2012)
The gut microbiota refers to the trillions of microorganisms residing in the intestine and is integral in multiple physiological processes of the host. Recent research has shown that gut bacteria play a role in metabolic disorders such as obesity, diabetes, and cardiovascular diseases. The mechanisms by which the gut microbiota affects metabolic diseases are by two major routes: (1) the innate immune response to the structural components of bacteria (e.g., lipopolysaccharide) resulting in inflammation and (2) bacterial metabolites of dietary compounds (e.g., SCFA from fiber), which have biological activities that regulate host functions. Gut microbiota has evolved with humans as a mutualistic partner, but dysbiosis in a form of altered gut metagenome and collected microbial activities, in combination with classic genetic and environmental factors, may promote the development of metabolic disorders. This paper reviews the available literature about the gut microbiota and aforementioned metabolic disorders and reveals the gaps in knowledge for future study.